Intramedullary Nailing Versus External Fixation in the Treatment of Open Tibial Fractures in Tanzania: Results of a Randomized Clinical Trial. (20th May 2020) - Haonga, Billy T.; Liu, Max; Albright, Patrick; Challa, Sravya T.; Ali, Syed H.; Lazar, Ann A.; Eliezer, Edmund N.; Shearer, David W.; Morshed, Saam
Abstract : Background: Open tibial fractures are common injuries in low and middle-income countries, but there is no consensus regarding treatment with intramedullary nailing versus external fixation. The purpose of the present study was to compare the outcomes of initial treatment with intramedullary nailing or external fixation in adults with open tibial fractures. Methods: We conducted a randomized clinical trial (RCT) at a tertiary orthopaedic center in Tanzania. Adults with acute diaphyseal open tibial fractures were randomly assigned to statically locked, hand-reamed intramedullary nailing or uniplanar external fixation. The primary outcome was death or reoperation for the treatment of deep infection, nonunion, or malalignment. Secondary outcomes included quality of life as measured with the EuroQol-5 Dimensions (EQ-5D) questionnaire, radiographic alignment, and healing as measured with the modified Radiographic Union Scale for Tibial fractures (mRUST). Results: Of the 240 patients who were enrolled, 221 (92.1%) (including 111 managed with intramedullary nailing and 110 managed with external fixation) completed 1-year follow-up. There were 44 primary outcome events (with rates of 18.0% and 21.9% in the intramedullary nailing and external fixation groups, respectively) (relative risk [RR] = 0.83 [95% confidence interval (CI), 0.49 to 1.41]; p = 0.505). There was no significant difference between the groups in terms of the rate of deep infection. Intramedullary nailing was associated with a lower risk of coronal malalignment (RR = 0.11 [95% CI, 0.01 to 0.85]; p = 0.01) and sagittal malalignment (RR = 0.17 [95% CI, 0.02 to 1.35]; p = 0.065) at 1 year. The EQ-5D index favored intramedullary nailing at 6 weeks (mean difference [MD] = 0.07 [95% CI = 0.03 to 0.11]; p < 0.001), but this difference dissipated by 1 year. Radiographic healing (mRUST) favored intramedullary nailing at 6 weeks (MD = 1.2 [95% CI = 0.4 to 2.0]; p = 0.005), 12 weeks (MD = 1.0 [95% CI = 0.3 to 1.7]; p = 0.005), and 1 year (MD = 0.8 [95% CI = 0.2 to 1.5]; p = 0.013). Conclusions: To our knowledge, the present study is the first RCT assessing intramedullary nailing versus external fixation for the treatment of open tibial fractures in sub-Saharan Africa. Differences in primary events were not detected, and only coronal alignment significantly favored the use of intramedullary nailing. Level of Evidence: Therapeutic Level I . See Instructions for Authors for a complete description of levels of evidence.